On the Economic Origins of Concerns Over Women’s Chastity - Becker, Anke (Review of Economic Studies, 2025)
Abstract This article studies the origins and function of customs and norms that intend to keep women from being promiscuous. Using large-scale survey data from more than 100 countries, I test the anthropological theory that a particular form of pre-industrial subsistence—pastoralism—favoured the adoption of such customs and norms. Pastoralism was characterized by frequent and often extended periods of male absence from the settlement, implying difficulties in monitoring women’s behaviour and larger incentives to imposing restrictions on women’s promiscuity. The article shows that women from historically more pastoral societies (i) are subject to stronger anti-abortion attitudes; (ii) are more likely to have undergone infibulation, the most invasive form of female genital cutting; (iii) are more restricted in their freedom of mobility; and (iv) adhere to more restrictive norms about women’s promiscuity. At the historical society level, pastoralism predicts patrilocality, the custom of living close to the husband’s family after marriage, allowing them to monitor the bride. Instrumental variable estimations that make use of the ecological determinants of pastoralism support a causal interpretation of the results. I also provide evidence that the mechanism behind these patterns is male absence, rather than male dominance, per se, or historical economic development.